Pengaruh Gaya Hidup, Harga dan Kualitas Produk Terhadap Keputusan Pembelian Peralatan Outdoor Merek Eiger di Kota Banjarmasin (Studi Pada Mahasiswa Pencinta Alam Di Kota Banjarmasin) - Muhammad Gazali; Setio Utomo; Maryono Maryono (Smart Business Journal, 2021)
This study aims to determine the effect of Lifestyle, Price and Product Quality on Purchasing Decisions. The research approach used is a quantitative approach. The population is all Nature Lover Students in the city of Banjarmasin. The sample used in this study was 91 respondents. This research uses Proportional Stratified Random technique. Data analysis techniques using Multiple Linear Regression Analysis Techniques. The results in this study indicate that Lifestyle (X1) partially has a significant and positive effect on purchasing decisions with a sig t value of 0.001 below 0.05 and Price (X2) partially has a significant effect on a purchasing decision with a sig t value of 0.028 below 0.05 and also Product Quality (X3) partially has a significant effect on purchasing decisions with a sig t value of 0,000 below 0.05. Tests together show there is a significant simultaneous influence on Lifestyle (X1), Price (X2) and Product Quality (X3) on purchasing decisions (Y) because the sig f value of 0,000 is below 0.05. Keywords:  Lifestyle, Price, Product Quality, purchasing decisions